Kárpátalja a magyar hadtörténeti földrajzban - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2016)
The Trans-Carpathian region was a geographical periphery throughout the history of Hungary and, as a functional space due to its geographical location, it played a relatively less important role in Hungarian history than other regions in the Carpathian Basin. However, this geographical periphery had gained more weight in certain historical eras from a military geographical aspect. External political forces, as well as social and political processes inside and outside the Carpathian Basin, suddenly increased the landscape’s military geographical energy. As a result, Rákóczy’s war of independence had its core area in this region. The Trans-Carpathian region functioned as an important area of defense mainly during the Mongol invasion of 1241-1242 as well as during the two World Wars, while it also sporadically became the focus of attention during Hungary’s larger revolutions and wars of independence (1848-1849, 1918-1919, 1956). The present study discusses these changes in geographical function based on military purposes. In addition, it also considers the notion of Gyula Prinz regarding the northeastern regions of the Carpathian Basin – similarly to the western ones – as being areas of foreign cultural influence. However, the extent and strength of this influence greatly depended on the condition and power of states on the other side of the Carpathian Mountains. Thus, the changes in the political spatial structure of Eastern Europe also need to be noted.